Divergent processes and trends of desertification in Inner Mongolia and Mongolia - Guo, X; Chen, R; Thomas, D; Li, Q; Xia, Z; Pan, Z (Wiley, 2021)
Desertification and the expansion of deserts are regarded as a major threat to human livelihoods and ecosystem services, as well as achieving Sustainable Development Goals. Humans have been recognized as significant agents in the expansion of desert‐like conditions, through the agency of desertification/land degradation, and through contributions to global climate change. Yet, how desertification changes and whether human or climate change drives these processes and trends over the whole Mongolia Plateau is still not clear. Here we first use MODIS data for 2000–2019 to assess the long‐term vegetation changes across the Mongolian Plateau, both in Inner Mongolia of PR China and the Mongolian People's Republic. We then appied a General Linear Model to analyze the additional climate and human attribute data sets to explore relationships between the observed desert extent reduction and their potential drivers. Results show that from 2000–2019, desert extent declined by over 7%, comprised of an almost 11% reduction in Inner Mongolia and 5% reduction in Mongolia, and a reduction in the degree of desert conditions, as measured by vegetation cover grades, across the whole region (37.5% decline ‐ one grade in PR China, 28.75% in Mongolia). The majority of desert area reduction occurs in the northern and eastern areas of the Mongolia Plateau. We found that the main drivers of changing desert extent is not because of a reduction in human pressures on the land, but an increasing trend of both precipitation and temperature, which explains over 75% of all the observed changes. Besides, urbanization, and a reduction of population pressures on the land, contribute to most of the remaining changes. Our results suggest that although the climate has been the primary driver of changing desert area and severity, human interventions have played an important role, although the way it intervenes and the intensity varies in Inner Mongolia and Mongolia. Human's active response to land degradation in the desert contributes to more land restoration in Inner Mongolia than in Mongolia.